First-principles calculation of magnetic, structural, dynamic, electronic, elastic, thermodynamic and thermoelectric properties of Co2ZrZ (Z = Al, Si) Heusler alloys - Sâad Essaoud (Université de M'sila, 2021)
Electronic, magnetic, dynamic, elastic, ‎thermodynamic, and thermoelectric properties for Co2-based full Heusler alloys are investigated theoretically. The full potential–linearized augmented plane wave (FP-LAPW) method within ‎density functional theory (DFT) incorporated on WIEN2k code is employed in ‎our calculation. Through this study, we found that the FM-L21 is the most magnetic-structure stable phase for both Co2ZrAl and Co2ZrSi compounds, as well as they, are dynamically stable where all the calculated of the optic and acoustic phonon frequencies have positive values. Band structure calculation demonstrated ‎that all compounds exhibit band gaps of about 0.88 and 1.54 eV using mBJ-GGA potentials for Co2ZrAl and Co2ZrSi in a localized minority spin channel (unlike the other ‎direction which appears a metallic behavior) with high spin polarization (100%) in its ground ‎state. Under high pressure, both compounds keep the same electronic behavior in both spins’ ‎channels with a little decreasing in gap energy, unlike the total magnetic moment which doesn’t ‎change. The semi-local Boltzmann ‎transport theory has been used to investigate thermoelectric properties and we found that both compounds exhibit a high Seebeck coefficient and high-power factor up to 1.25 mV/K for ‎Co2ZrSi. Also, the quasi-harmonic model has been applied to study the ‎temperature effect on heat capacities at ‎constant volume, in which entropy, Debye temperature and lattice ‎thermal conductivity are analyzed and ‎discussed. To get more information about the elastic ‎behavior; the elastic stability in the equilibrium state and under two pressures values (12 ‎GPa and 24 GPa) are found. The findings predicted the stability of these ‎compounds’ properties with and without pressure, which makes them candidate materials for ‎devices fabrication ‎in several areas such as spinotronic, thermoelectric, shape-memory and spin ‎filters.
Keywords: Heusler Alloys, Half-metallic, Seebeck Coefficient, Electrical and Thermal Conductivity Coefficients, Elastic Constants.